Pulmonary Vein Isolation to Reduce Future Risk of Atrial Fibrillation in Patients Undergoing Typical Flutter Ablation: Results from a Randomized Pilot Study (REDUCE AF). (26th May 2015) - MOHANTY, SANGHAMITRA; NATALE, ANDREA; MOHANTY, PRASANT; DI BIASE, LUIGI; TRIVEDI, CHINTAN; SANTANGELI, PASQUALE; BAI, RONG; BURKHARDT, J. DAVID; GALLINGHOUSE, G. JOSEPH; HORTON, RODNEY; SANCHEZ, JAVIER E.; HRANITZKY, PATRICK M.; et al.
Benefits of PVI in Patients with Atrial Flutter: Background: This study examined incidence of AF following cavotricuspid isthmus (CTI) ablation alone or CTI plus prophylactic pulmonary vein isolation (PVI) in patients presenting with isolated atrial flutter (AFL) with no history of AF. Methods and Results: We enrolled 216 patients with isolated typical atrial flutter and randomized them to CTI alone (group 1, n = 108, 61.2 ± 9.7 year, 75% male) or CTI+PVI ablation (group 2, n = 108, 62.4 ± 9.3 year, 73% male). Insertible loop recorder (ILR) was implanted in 21 and 19 patients from groups 1 and 2, respectively. Remaining patients were monitored with event recorders, ECG, 7‐day Holter. Follow‐up period was for 18 ± 6 months. Compared to group 1, group 2 had significantly longer procedural duration (75.9 ± 33 min vs. 161 ± 48 min [P < 0.001]) and fluoroscopy time (15.9 ± 12.3 min vs. 56.4+21 min [P < 0.001]). At the end of follow‐up, 65 (60.2%) in group 1 and 77 (71.3%) in group 2 were arrhythmia free off‐AAD (log‐rank P = 0.044). A subgroup analysis was performed with 55 year age cut‐off. In the <55 age group the CTI only population had similar success as in CTI+PVI, (21 of 24 [83.3%] vs. 19 of 22 [86.4%], respectively, log‐rank P = 0.74). In the ≥55 group, having CTI+PVI showed significantly higher success compared to CTI only; 45 of 84 (53.6%) were AF/AT free in CTI only group versus 58 of 86 (67.4%) with CTI+PVI (log‐rank P = 0.029). Conclusion: Prophylactic PVI reduced new‐onset AF in patients with lone atrial flutter.